1'-Acetoxyeugenol Acetate Isolated from Thai Ginger Induces Apoptosis in Human Ovarian Cancer Cells by ROS Production via NADPH Oxidase - Ju-Yeon Choi; Na-Kyung Lee; Yi-Yue Wang; Joon-Pyo Hong; So Ri Son; Da-Hye Gu; Dae Sik Jang; Jung-Hye Choi (MDPI AG, 2022)
The rhizomes of Alpinia galanga (Thai ginger) have been used extensively as a spice in Southeast Asian and Arabian cuisines and reported to possess a wide range of biological properties, such as antioxidant, antimicrobial, and antibacterial. However, the specific molecular and cellular mechanisms underlying the anti-tumor effects induced by Thai ginger and its corresponding active compounds have been poorly characterized. We found that upon EtOH extraction, Thai ginger extract exhibits cytotoxic activity (IC50 < 10 μg/mL) and triggers cell death via caspase-dependent apoptosis in human ovarian cancer cells. Among the three major compounds isolated from the extract, 1'-acetoxyeugenol acetate (AEA) exhibited potent cytotoxic activity in human ovarian cancer cells, SKOV3 and A2780. AEA induced apoptotic cell death through the activation of caspases-3 and -9. Notably, AEA enhanced the intracellular levels of reactive oxygen species (ROS), and the application of an antioxidant markedly reversed AEA-induced apoptosis of ovarian cancer cells. The knockdown of p47phox, a subunit of NADPH oxidase, suppressed both the pro-apoptotic and ROS-inducing effects of AEA. Additionally, the activation of the mitogen-activated protein kinase (MAPK) pathway by AEA through ROS regulation was found to be involved in AEA-induced apoptosis. Altogether, these results suggest that AEA exhibits potent apoptosis-inducing activity through the activation of the intrinsic pathway via ROS-mediated MAPK signaling in human ovarian cancer cells.